El maltrato infantil y su incidencia en el rendimiento escolar en la asignatura de computación de los estudiantes de cuarto año de educación básica “General Rumiñahui”., periodo 2013-2014. Lineamientos alternativos - Castillo Luzuriaga, Josefina Elizabeth (2014)
The thesis entitled: CHILD ABUSE AND ITS IMPACT ON SCHOOL PERFORMANCE IN THE COURSE OF COMPUTING THE FOURTH YEAR STUDENTS OF BASIC EDUCATION AND EARLY CHILDHOOD EDUCATION CENTER SCHOOL OF BASIC EDUCATION "GENERAL RUMIÑAHUI". PERIOD 2013 - 2014 ALTERNATIVE GUIDELINES, their study is important because it will allow to analyze the causes of child abuse and its impact on school performance. The overall objective is: To analyze child abuse and its impact on school performance computing subject of Fourth Year students of Basic Education Early Childhood Education Center and School of Basic Education "General Rumiñahui". Period 2013-2014. It is aimed to counter this problem, which has been applied in a survey form 6 teachers, a survey form to 35 parents and 35 students; product results statistical information presented in the body of the thesis, was evident through research that teachers are not trained to identify cases of child abuse in their students that directly affect learning, was obtained affecting their intellectual abilities and social. In this situation, we have designed an intervention proposal, consisting of a seminar-workshop for teachers and parents, so that families punish their children often learn positive discipline techniques and behavior development children, to control the abuse of children who are victims of the part of adults, affecting their learning performance.